2008
DOI: 10.1016/j.cyto.2007.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum levels of IL-1ra in children with Plasmodium falciparum malaria are associated with increased severity of disease

Abstract: Animal models suggest that cytokines and chemokines play a role in cerebral malaria (CM) pathogenesis, but levels of a number of cytokines and chemokines thought to be important in the pathogenesis of other infectious diseases are not well characterized in children with CM. Serum levels of granulocyte-colony stimulating factor (G-CSF), interleukin-1 receptor antagonist (IL-1ra), interleukin-8 (IL-8) and monocyte chemoattractant protein-1 (MCP-1) were measured in 77 children with CM, 70 children with uncomplica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 17 publications
5
48
0
Order By: Relevance
“…The early inflammatory response to HZ was first triggered by enhanced IL-1␤ transcription 0 to 2 h after HZ phagocytosis ended and then reinforced (4 h after phagocytosis) by increased expression of MMP-9, TNF-␣, and IL-1RA, a cytokine that was recently connected to increased severity of cerebral malaria (CM) (25). At this time, either macroarray analysis or real-time RT-PCR also detected enhanced expression of several molecules belonging to the chemokine class, a vast family of chemoattractant molecules involved in monocyte migration and neutrophil recruitment (see reference 30 for a review).…”
Section: Discussionmentioning
confidence: 99%
“…The early inflammatory response to HZ was first triggered by enhanced IL-1␤ transcription 0 to 2 h after HZ phagocytosis ended and then reinforced (4 h after phagocytosis) by increased expression of MMP-9, TNF-␣, and IL-1RA, a cytokine that was recently connected to increased severity of cerebral malaria (CM) (25). At this time, either macroarray analysis or real-time RT-PCR also detected enhanced expression of several molecules belonging to the chemokine class, a vast family of chemoattractant molecules involved in monocyte migration and neutrophil recruitment (see reference 30 for a review).…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of a reliable laboratory test that accurately identifies individuals at risk of developing fatal CM would be a valuable tool. Human studies have revealed tight association between levels of specific chemokines and CM mortality [4,5,12,41,[43][44][45]67]. Thus, understanding the alterations in cytokine or chemokine homeostasis in CM patients will elucidate the underlying pathogenesis and identify potential predictive prognostic biomarkers for CM mortality.…”
Section: Discussionmentioning
confidence: 99%
“…These observations attracted interest in investigating the trafficking pathways by which these cells are recruited to target organs and the potential contribution of chemokines to severe malaria (13). Recent studies revealed that circulating levels of various chemokines, including CCL4, CXCL4, CXCL8, and CXCL10 (also known as IFN-g-inducible protein 10), are significantly elevated in CM cases compared with mild malaria cases or healthy control individuals (14)(15)(16)(17)(18). Among these chemokines, CXCL10 appears to be the most accurate predictor of CM mortality (15,18).…”
mentioning
confidence: 99%